Nutritional Evaluation of Menus Regarding Nutritional Adequacy for Students at Al-Bahjah Islamic Boarding School in Cirebon Regency - Sholichin; Alina Hizni; Diyah Sri Yuhandini; Dewi Vimala (Media Informasi, 2026)
Background: Islamic boarding schools are Islamic-based educational institutions that provide daily meals for students. Al-Bahjah Islamic Boarding School serves approximately 4,500 meals per day.Objective: This study aimed to evaluate the nutritional content of meals provided in relation to students’ nutritional adequacy.Method: This quantitative descriptive observational study used a cross-sectional approach and was conducted from May to October 2025 at Al-Bahjah Islamic Boarding School, Cirebon Regency. Respondents included the head of the kitchen, food processing staff, and servers. Data on menu composition were obtained through food weighing and analyzed using the 2020 Indonesian Food Composition Table. Nutritional adequacy standards were based on the Regulation of the Minister of Health No. 28 of 2019, according to students’ age and gender. The adequacy level was determined by comparing the menu nutrient content with daily nutritional requirements.Results: The average nutrient content of meals consumed by students was 1,605 kcal of energy, 57 g protein, 40 g fat, and 249 g carbohydrates. The average nutritional adequacy requirement was 2,183 kcal energy, 63 g protein, 73 g fat, and 322 g carbohydrates. Consequently, the energy adequacy level reached 74% (insufficient), protein 89% (insufficient), and fat 56% (very insufficient). Conclusion: The meals provided at Al-Bahjah Islamic Boarding School did not meet students’ nutritional requirements. It is recommended to include additional snacks contributing about 20% of daily nutritional adequacy to improve students’ overall nutrient intake.